A TOP NIGHT: Social Protest, Masculinity and the Culture of Drinking Violence - TOMSEN, STEPHEN (The British Journal of Criminology, 1997)
Although a wide research literature suggests a regular connection between drinking, violence and social disorder, much doubt remains as to the actual nature and significance of this link. Some strong insights into this are provided by a dual consideration of the tie between masculine social identity and heavy group drinking, and the importance of issues of male honour in the social interaction that leads to much violent behaviour. But as well as this, information from the author's detailed ethnographic study of assaults in public drinking venues illuminates the subjective experience of participation in acts of disorder and violence. This is filtered through understandings of certain forms and aspects of popular leisure as entailing social protest and resistance to middle class morality. Although masculinist and frequently destructive, this violence is interpreted by many drinkers as providing a liberating and attractive sense of release, group pleasure and carnival.